Growth and Characterization of a New Non-Linear Optical Crystal: Urea Thiourea Zinc Chloride - Madhurambal, G.; Mariappan, M. (Asian Journal of Chemistry, 2010)
Urea thiourea zinc chloride (UTZC) a new semi-organic non-linear optical material has been synthesized. Single crystals of UTZC have been grown by slow evaporation of saturated aqueous solution at room temperature. The spectral bands have been compared with urea, thiourea, bis thiourea zinc chloride (BTZC).